The Implementation of Process Approach to Increase University Students’ Historical Academic Writing Skills Based On Oral Stories in SWCU - Sunardi Sunardi; Tri Widiarto; Listyanto Aji Nugroho (Universitas Kristen Satya Wacana, 2023)
This research aimed to investigate the effects of the process approach in developing students’ skills in writing scientific articles based on historical folklore. The subject of this study were 90 Satya Wacana Christian University students during the first semester of the 2021/2022 academic year. A qualitative approach was used in this study. The primary source of the data was the teaching-learning process in an academic writing class using a process approach. The procedure applied in this research was planning, acting, analyzing data, and report writing. Data were collected using field notes, teaching-learning process documentation, and learning outcomes. The data analysis was conducted through a series of data collection, data reduction, data presentation, and drawing some conclusions. Based on the results and discussions, it was concluded that the process approach improved university students’ academic writing skills. This increase could be observed in both the process and the results. The process approach improved students’ activeness during the teaching and learning process, academic writing skills, and the classroom atmosphere. Hence, the implementation of the process approach can increase university students’ skills in writing academic papers.